2021
DOI: 10.21203/rs.3.rs-1093241/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mindfulness-Based Online Intervention Increases Well-Being And Decreases Stress After Covid-19 Lockdown

Abstract: Mindfulness interventions were shown to be effective in improving well-being and reducing perceived stress in several conditions. These effects were also found in online mindfulness-based training, especially on employees in organizational environments. The aim of this study was to test the effectiveness of online mindfulness intervention on healthy employees especially after the first Italian Covid-19 lockdown.Participants in the intervention group underwent an 8-week mindfulness online training program based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The increasing mental health issues during the COVID-19 pandemic and the challenges of delivering face-to-face interventions have increased the demand for online interventions. Online interventions are easily scalable, more accessible, allow for adherence to social distancing, have greater anonymity, and reduce delivery costs (Bossi et al, 2021). Several studies evaluated the efficacy of online mindfulness interventions prior to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing mental health issues during the COVID-19 pandemic and the challenges of delivering face-to-face interventions have increased the demand for online interventions. Online interventions are easily scalable, more accessible, allow for adherence to social distancing, have greater anonymity, and reduce delivery costs (Bossi et al, 2021). Several studies evaluated the efficacy of online mindfulness interventions prior to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with higher levels of PA are more likely to care for themselves (89) and show great potential in health behavior learning (90). PA can help people cope with PR, especially after the COVID-19 lockdown (91). In this study, the influence of PA on PB was greater than that of NA.…”
Section: Discussionmentioning
confidence: 56%
“…A study on operating room staff found that providing them with 30-min of music therapy three times a day for a consecutive month significantly decreased their emotional exhaustion, representing improved job burnout (51). In another pilot study, researchers chose mindfulness therapy based on an online app, which has also been shown to help reduce the stress and negative emotions of medical and non-medical participants, thereby improving burnout (52,53). We therefore recommend the use of non-drug interventions such as online mindfulness therapy or music therapy to help medical staff with job burnout during the COVID-19 pandemic.…”
Section: Suggestion and Potentially Helpful Methodsmentioning
confidence: 99%